2009
DOI: 10.4065/84.3.255
|View full text |Cite
|
Sign up to set email alerts
|

“I'm Going Home”: Discharges Against Medical Advice

Abstract: Discharge against medical advice (AMA), in which a patient chooses to leave the hospital before the treating physician recommends discharge, continues to be a common and vexing problem. This article reviews the prevalence, costs, predictors, and potential interventions for this clinical problem. Between 1% and 2% of all medical admissions result in an AMA discharge. Predictors of AMA discharge, based primarily on retrospective cohort studies, tended to be younger age, Medicaid or no insurance, male sex, and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
236
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(273 citation statements)
references
References 62 publications
15
236
4
2
Order By: Relevance
“…The patient factors associated with AMA discharge have been reasonably consistent over time, and include lower socioeconomic class, male sex, younger age, Medicaid or no insurance, and a history of substance abuse. 1 Commonly reported patient reasons for leaving AMA include personal or financial obligations, feeling better or receipt of social assistance payments. 9,10 The stated aim of this research was to generate potential interventions that could mitigate the number of such discharges.…”
Section: Predictors Of Ama Dischargementioning
confidence: 99%
See 1 more Smart Citation
“…The patient factors associated with AMA discharge have been reasonably consistent over time, and include lower socioeconomic class, male sex, younger age, Medicaid or no insurance, and a history of substance abuse. 1 Commonly reported patient reasons for leaving AMA include personal or financial obligations, feeling better or receipt of social assistance payments. 9,10 The stated aim of this research was to generate potential interventions that could mitigate the number of such discharges.…”
Section: Predictors Of Ama Dischargementioning
confidence: 99%
“…[1][2][3] Compared to patients discharged conventionally, 30-day readmission rates for patients discharged AMA are 20-40 % higher, 3,4 and their adjusted relative risk of 30-day mortality may be increased as much as 10 %. 2 Despite the excess morbidity, health care costs, and associated stigma, AMA discharges are relatively unexamined.…”
Section: Introductionmentioning
confidence: 99%
“…6 In practice, however, AMA discharges are often emotionally charged for both patients and providers, and, in the high-stress setting of AMA discharge, providers may be confused about their roles. [7][8][9] The demographics of patients who leave AMA have been well described. Compared with conventionally discharged patients, AMA patients are younger, more likely to be male, and more likely a marginalized ethnic or racial minority.…”
mentioning
confidence: 99%
“…Studies have suggested that pa ents with history of alcohol/drug abuse mistrust medical care givers, and also their addic ve behaviour -the desire to get more drug and [17][18] alcohol once discharged is high.…”
Section: Atreya a Et Almentioning
confidence: 99%